Design of a rotor blade tip for the investigation of dynamic stall in the transonic wind-tunnel Göttingen. (4th July 2016) - Lütke, B.; Nuhn, J.; Govers, Y.; Schmidt, M.
ABSTRACT: The aerodynamic and structural design of a pitching blade tip with a double-swept planform is presented. The authors demonstrate how high-fidelity finite element (FE) and computational fluid dynamic (CFD) simulations are successfully used in the design phase. Eigenfrequencies, deformation, and stress distributions are evaluated by means of a three-dimensional (3D) FE model. Unsteady Reynolds-averaged Navier-Stokes (RANS) simulations are compared to experimental data for a light dynamic stall case at Ma = 0.5, Re = 1.2 × 10 6 . The results show a very good agreement as long as the flow stays attached. Tendencies for the span-wise location of separation are captured. As soon as separation sets in, discrepancies between experimental and numerical data are observed. The experimental data show that for light dynamic stall cases at Ma = 0.5, a factor of safety of FoS = 2.0 is sufficient if the presented simulation methods are used.